2018
DOI: 10.1155/2018/1350195
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity, Low Dietary Diversity, and Early Marriage Were Predictors for Undernutrition among Pregnant Women Residing in Gambella, Ethiopia

Abstract: Background. Maternal undernutrition affects the health of both mothers and children and, as a result, has broad impacts on economic and social development. Objective. The aim of this study was to assess magnitude of undernutrition and associated factors among pregnant women in Gambella town, 2014. Methods. Community based cross-sectional study was conducted on 338 randomly selected pregnant women from March to April 2014. Bivariate and multivariable logistic regressions were used for data analysis. Result. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 9 publications
13
49
8
2
Order By: Relevance
“…Prior research in Samre district of Northern Ethiopia, showed that the proportion of lactating mothers who had less than three meals in the last 24-h preceding their survey was 27% [5], which is comparable with our findings. However, this prevalence reduced to 8.4% in the non-fasting period, which is comparable with the prevalence (7.5%) of pregnant women in Gambela town, Western Ethiopia [70]. Similarly, the number of meals eaten both by fasting and non-fasting mothers were significantly increased after two months of fasting period.…”
Section: Discussionsupporting
confidence: 50%
“…Prior research in Samre district of Northern Ethiopia, showed that the proportion of lactating mothers who had less than three meals in the last 24-h preceding their survey was 27% [5], which is comparable with our findings. However, this prevalence reduced to 8.4% in the non-fasting period, which is comparable with the prevalence (7.5%) of pregnant women in Gambela town, Western Ethiopia [70]. Similarly, the number of meals eaten both by fasting and non-fasting mothers were significantly increased after two months of fasting period.…”
Section: Discussionsupporting
confidence: 50%
“…The variation might be due to distinctions in MUAC cut of value, and the socio-culture distinctions between Ethiopia and the other counties. The present study nding was lower than those of studies done in other areas of Ethiopia reported 72%, 34%, 31.8%, 31.4%, 30.3% and 28.6% (26,27,(37)(38)(39)(40). In the current study prevalence of maternal undernutrition shows a little decrement in compared to previous studies done in the study area.…”
Section: Discussioncontrasting
confidence: 84%
“…As Ethiopia is one of the developing countries, the present review recorded signi cant number of pregnant women were under nourished. This may be due to the majority of Ethiopian population were rural residence with no formal education, more of adolescent, higher parity status, poor dietary diversity and higher food insecurity, leads to higher risk of malnutrition [22,46,58,60]. In addition, the national ante natal care utilization is still poor which will be a constraint to supply iron for pregnant women [60].…”
Section: Discussionmentioning
confidence: 99%
“…These articles were from six regional state and two cities of Ethiopia. Eight studies were done in Oromo regional state [25,26,28,30,31,33,46,47], six articles in Amhara region [32,[48][49][50][51][52], four articles from South Nation and Nationality of People (SNNP) [27,34,53,54], two articles in Tigray [29,55] and in Addis Ababa (AA) [56], Dire Dawa [57], Gambella [58] and Ethiopian Somalia [59] shared single articles for each.…”
Section: Explanation For Original Studiesmentioning
confidence: 99%